The interaction of temperature and relative humidity affects the main aromatic components in postharvest Torreya grandis nuts. (30th January 2022) - Hu, Yuanyuan; Zhang, Zuying; Hua, Bin; Tao, Liu; Chen, Wenchao; Gao, Yadi; Suo, Jinwei; Yu, Weiwu; Wu, Jiasheng; Song, Lili
Highlights: Terpenes were the predominant aromatic compounds in harvested raw T. grandis nuts. High humidity treatments enhanced terpene formation. High humidity treatments promoted terpenes by stimulating d -limonene synthesis. Abstract: The postharvest ripening stage is necessary for Torreya grandis ( T. grandis ) nuts to complete aromatic synthesis, which requires appropriate temperature and relative humidity (RH). Currently, scarce information is available regarding the changes in aroma profiles in T. grandis nuts and the relationship with their response to different environmental conditions. Therefore, the interaction of temperature (20 °C or 30 °C) and relative humidity (70% RH or 90% RH) was investigated on aromatic substances after harvest. The results showed that 56 aromatic components were detected by a gas chromatography-mass spectrometer (GC–MS) and mainly divided into five categories, among which terpenes were the most abundant (56.2–86.7%). Principal component analysis (PCA) showed that both temperature and humidity can affect the aroma composition, and terpenes were mainly influenced by humidity. Specifically, d -limonene occupied the largest proportion of terpenes (63.0–90.8%) and was significantly upregulated by high humidity.